Homogenous catalysis of peroxynitrite conversion to nitrate by diaryl selenide: a theoretical investigation of the reaction mechanism - Xue, Yuan; Salmon, Carrie; Gogonea, Valentin (Frontiers in Chemistry, 2024)
Quenching peroxynitrite (a reactive oxidant species) is a vital process in biological systems and environmental chemistry, (Radi, 2018, Koppenol, 1999) as it balances redox and mitigates damaging effects in living cells and the environment. Here, we report a systematic analysis on the mechanism of transforming peroxynitrite into nitrate by diarylselenide in water. Through quantum mechanical calculations, this work probes the dynamic isomerization of peroxynitrite in a homogeneous catalytic environment. The mapped potential energy surfaces (PES) of various methods in conjunction with different basis sets suggest that the isomerization mechanism includes four major steps: the reaction of peroxynitrite with diarylselenide via an oxygen-bound selenium, selenium oxidation in the presence of an appropriate oxidant, oxygen transfer and ultimately the generation of nitrate. The molecular orbital analysis suggests a substituent effect in the aromatic ring of diarylselenide for this reaction. Changes in both molecular orbitals and electrostatic potential highlight the significance of the electron transfer step in ensuring the progression of this reaction.